2022
DOI: 10.1101/2022.02.18.480872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 has not emerged in roe, red or fallow deer in Germany or Austria during the COVID 19 pandemic

Abstract: Spillover of SARS-CoV-2 to North American white tailed deer (Odocoileus virginianus) has been documented. We evaluated pre and pandemic exposure of German and Austrian deer species using a SARS-CoV-2 pseudoneutralization assay. In stark contrast to North American white tailed deer, we found no evidence of SARS-CoV-2 exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Neutralization profile of each sample is shown in Figure 3(a), and the titer values (IC50) are shown in Figures 3(b) and 3(c). All samples in this study seropositive for sVNT were also positive for cVNT, in contrast to other studies that reported deer sera with cross-reactive antibodies against SARS-CoV-2 RBD, with a positive result for sVNT but negative for cVNT, probably induced by another deer coronavirus antigenically related to SARS-CoV-2 [28].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Neutralization profile of each sample is shown in Figure 3(a), and the titer values (IC50) are shown in Figures 3(b) and 3(c). All samples in this study seropositive for sVNT were also positive for cVNT, in contrast to other studies that reported deer sera with cross-reactive antibodies against SARS-CoV-2 RBD, with a positive result for sVNT but negative for cVNT, probably induced by another deer coronavirus antigenically related to SARS-CoV-2 [28].…”
Section: Resultscontrasting
confidence: 99%
“…Given the high prevalence of SARS-CoV-2 infection in North American deer, numerous attempts to search for the virus in European deer have been made, but have so far been unsuccessful. SARS-CoV-2 surveys conducted in Germany and Austria during 2020-2022 resulted negative in European roe deer (ERD, Capreolus capreolus), red deer (RD, Cervus elaphus), and fallow deer (FD, Dama dama) [28,29]. Similarly, serological surveys in UK, conducted from January 2020 to May 2021, resulted negative [30], as well as in Belgium [31].…”
Section: Introductionmentioning
confidence: 99%